1978
DOI: 10.1099/00207713-28-1-82
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas pseudoflava, a New Species of Hydrogen-Oxidizing Bacteria: Its Differentiation from Pseudomonas flava and Other Yellow-Pigmented, Gram-Negative, Hydrogen-Oxidizing Species

Abstract: Five new strains of yellow-pigmented, gram-negative, motile, hydrogen-oxidizing bacteria were isolated; each served as a host for simultaneously isolated bacteriophages. These isolates and two additional strains were compared with other gram-negative, hydrogen-oxidizing bacteria with respect to morphology; nutritional and biochemical properties; growth parameters; cytochrome content; pigment production; susceptibility to bacteriophages, bacteriostatic agents, and antibiotics; deoxyribonucleic acid base composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 24 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…Motile by means of one, rarely two, polar to subpolar flagella. (4,48). Nutritional and enzymatic features are listed in Table 7.…”
Section: Dna Base Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motile by means of one, rarely two, polar to subpolar flagella. (4,48). Nutritional and enzymatic features are listed in Table 7.…”
Section: Dna Base Compositionmentioning
confidence: 99%
“…Recently, Jenni et al (21) reported nitrogen fixation for a strain (strain NEU 2226) which they assigned to [Pseudornonus] pseudoJava, although this feature could not be detected in strain GA3T. Hydrogenophaga pseudoflava was isolated from soil, mud, and water by enrichment for hydrogen bacteria (4,33). The mean G+C content of the DNA is 66 to 69 mol%.…”
Section: Dna Base Compositionmentioning
confidence: 99%
“…5) and with HindIII restriction enzyme. Taken together with the data on the properties of the bacteriophage protein coats and on their biological relatedness (Auling, 1978;Auling et al I977), one can conclude that the three P. pseudoflava bacteriophages gd, ge and gfare identical.…”
Section: Fragmentation Analysis Of Bacteriophage Dnas With Restrictiomentioning
confidence: 72%
“…strain 2K1 has been described previously (12, 13), and a culture of this strain was deposited with the Deutsche Sammlung von Mikroorganismen, Gottingen, Federal Republic of Germany, under the number DSM 2082. Pseudornonus p s e u d o j a w GA3 (= DSM 1034) (2) The basal medium used for growth was the mineral medium described by Schlegel et al (20). One milliliter of trace elements solution SL6 of Pfennig (17) concentrated 10-fold was added to 1 ml of medium.…”
Section: Methodsmentioning
confidence: 99%
“…DNA-DNA reassociation was performed as previously described (2), and the degree of binding was calculated by using the formula of DeLey et al (7).…”
Section: Methodsmentioning
confidence: 99%